Changes in Leaf Litter Quality During Its Decomposition in a Tropical Planted Mangrove Forest (Can Gio, Vietnam) - Vinh, Truong Van; Allenbach, Michel; Linh, Khanh Tran Vu; Marchand, Cyril (Frontiers in Environmental Science, 2020)
Mangroves are highly productive ecosystems, being key components of trophic food chains along tropical coastlines. In Southern Vietnam, planted Rhizophora apiculata develops in the upper intertidal zone, while Avicennia alba naturally colonizes areas at lower elevation along tidal creeks. The main objective of this study was to quantify the seasonal variability of leaf litter decomposition rates considering that in previous studies we observed a strong influence of the monsoon on C and nutrients cycling within the mangrove and in adjacent creeks. We were also interested in changes in the quality of the leaf litter during its decomposition, focusing on nutrients, δ13C, and trace metals. To reach our goals, we used the litterbag technique. During the monsoon, leaf litter decay rates were increased in the Avicennia stand, most probably because of enhanced leaching resulting from a higher level of the river due to heavy rainfall. In addition, the enhanced decay rates measured in the Avicennia stand during the rainy season resulted in a strong 13C depletion, while 13C enrichment was measured in the other conditions. Elemental concentrations changes during decay were not clearly influenced by season, but depended on the element considered. K, Mg, Na, and Ca had t50 values lower than the one of the bulk material. P and S contents also rapidly decreased during the first decomposition stages, but these elements had longer t50 values than the bulk leaves. Conversely, an enrichment in most trace metals was observed during leaf litter decomposition whatever the season. We suggest that these metals were either trapped from the water column and the forest floor by organic molecules composing the litter, or subjected to litter decomposers uptake. Consequently, this study shows that the release or the uptake of elements during mangrove leaf litter decomposition varied with different parameters, which may have ecological implications on the nature of the elements exported towards adjacent ecosystems, and on their primary productivity.